2001
DOI: 10.1136/jmg.38.6.361
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 andBRCA2 mutation status and cancer family history of Danish women affected with multifocal or bilateral breast cancer at a young age

Abstract: Introduction-A small fraction of breast cancer is the result of germline mutations in the BRCA1 and BRCA2 cancer susceptibility genes. Mutation carriers frequently have a positive family history of breast and ovarian cancer, are often diagnosed at a young age, and may have a higher incidence of double or multiple primary breast tumours than breast cancer patients in general. Objectives-To estimate the prevalence and spectrum of BRCA1 and BRCA2 mutations in young Danish patients affected with bilateral or multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
25
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 29 publications
8
25
1
3
Order By: Relevance
“…The literature is not unanimous about the predictive value of multiple primary (ipsilateral or contralateral) breast cancers for finding a mutation. Our results are in agreement with the studies of Bergthorsson et al (2001), de la Hoya et al (2002 and Ford et al (1998); however, others failed to demonstrate such a predictive value (Couch et al, 1997;Steinmann et al, 2001). Male breast cancer in combination with a family history of breast/ovarian cancer was indicative of finding a BRCA2 mutation (P ¼ 0.002), which is consistent with a recent population-based British study (Basham et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…The literature is not unanimous about the predictive value of multiple primary (ipsilateral or contralateral) breast cancers for finding a mutation. Our results are in agreement with the studies of Bergthorsson et al (2001), de la Hoya et al (2002 and Ford et al (1998); however, others failed to demonstrate such a predictive value (Couch et al, 1997;Steinmann et al, 2001). Male breast cancer in combination with a family history of breast/ovarian cancer was indicative of finding a BRCA2 mutation (P ¼ 0.002), which is consistent with a recent population-based British study (Basham et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…The 5386insC mutation (also known as 5382insC) is common throughout Europe and is also a founder mutation in the Ashkenazi Jewish population. The 2594delC mutation constituted 18% of BRCA1 mutations in this study and was found at a similar frequency (17%) in the study of breast cancer cases from Denmark (20). The 3829delT and Q563X mutations have also been reported in studies from Sweden, suggesting that they may be Swedish/Danish founder mutations.…”
Section: Discussionsupporting
confidence: 52%
“…[13][14][15][16][17][18][19], but the data from the Danish population are much more limited. The largest study of BRCA1 and BRCA2 mutations to date from Denmark is the analysis of 103 multifocal or bilateral early-onset breast cancers, which identified mutations in 20% of cases (20). There are no reports in the literature describing the analysis of BRCA1 and BRCA2 in population-based ovarian cancer cases from Denmark.…”
mentioning
confidence: 99%
“…6 Although not highly quantitative, the Breast Cancer Information Core provides a valuable resource for tracking the occurrence of mutations throughout both the BRCA1 and BRCA2 genes. Also observed was a 5301insA change in BRCA2, reported several times in European women (29,31,32) and in women of Near and Middle Eastern descent in the Breast Cancer Information Core.…”
Section: Discussionmentioning
confidence: 99%